2010
DOI: 10.1080/17486021003706804
|View full text |Cite
|
Sign up to set email alerts
|

Model for analysis of fiber-reinforced clayey soil

Abstract: Fiber-reinforced soils have many applications in improving the response of clayey soils. In this paper, an analytical model for the analysis of fiberreinforced soil in the framework of modified cam clay model is presented. The analytical model is verified using experimental results from the standard undrained triaxial tests with pore water pressure measurements. Tests have been conducted on clayey soil specimens reinforced with randomly oriented discrete coir fibers with different percentages of fiber contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…The reinforcing role of short virgin synthetic fibres in coarse-grained soils with loose to dense states has been studied previously (Maher and Gray 1990;Nataraj 1997;Consoli et al 2007;Diambra et al 2007Diambra et al , 2010Chen and Loehr 2009;Hamidi and Hooresfand 2013;Miranda Pino et al 2015;and Jamsawang et al 2015). The behaviour of fibre-reinforced fine-grained soils has also been studied previously (Falorca et al 2006;Casagrande et al 2006;Özkul and Baykal 2007;Al-Akhras et al 2010;Babu and Chouksey 2010;Ekinci and Ferreira 2012;Maliakal and Thiyyakkandi 2013;Sadeghi andBeigi 2014 andBotero et al 2015;Khatri et al 2015;and Anggraini et al 2016). The reported research findings are in agreement in that fibre reinforcement improves the stress-strain behaviour, unconfined compression strength, shear strength and ductility of the soil and reduces the consolidation settlement of clay.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reinforcing role of short virgin synthetic fibres in coarse-grained soils with loose to dense states has been studied previously (Maher and Gray 1990;Nataraj 1997;Consoli et al 2007;Diambra et al 2007Diambra et al , 2010Chen and Loehr 2009;Hamidi and Hooresfand 2013;Miranda Pino et al 2015;and Jamsawang et al 2015). The behaviour of fibre-reinforced fine-grained soils has also been studied previously (Falorca et al 2006;Casagrande et al 2006;Özkul and Baykal 2007;Al-Akhras et al 2010;Babu and Chouksey 2010;Ekinci and Ferreira 2012;Maliakal and Thiyyakkandi 2013;Sadeghi andBeigi 2014 andBotero et al 2015;Khatri et al 2015;and Anggraini et al 2016). The reported research findings are in agreement in that fibre reinforcement improves the stress-strain behaviour, unconfined compression strength, shear strength and ductility of the soil and reduces the consolidation settlement of clay.…”
Section: Introductionmentioning
confidence: 90%
“…There are also several statistical models to predict the shear strength of fibrereinforced granular soils (Ranjan et al 1996;Babu and Vasudevan 2008) with input parameters including some or any of the following: fibre content, fibre aspect ratio, fibre surface friction, confining pressure, fibre length, cohesion and internal friction angle of the fibre-reinforced soil. Cam Clay constitutive model has also been reformulated to account for the estimation of the deviator stress of fibre-reinforced clays (Chen 2007;Babu and Chouksey 2010;Ibraim 2014 andNguyen andFatahi 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The failure occurred by the frictional slipping of the reinforcement up to a certain value known as the critical confining stress above which, the tensile strength of the fibre governed the failure. In the recent years, researchers have shown that fibre-reinforced soil is a potential composite material that improves the structural behaviour of soil and thus can be employed (Sivakumar Vasudevan, 2008a, 2008b;Sivakumar Babu and Chouksey, 2010). Researchers have performed the tests with different types of fibres varying their proportions and also studied their effects on the improvement of the soil characteristics.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The coir fibres have good strength and resistance to bio-degradation over a long period of time [6]. The uncon-fined compressive strength of black cotton soil reinforced with bitumen coated coir fibres shows marginal variation in strength as compared to uncoated coir fibres [7]. Numerical simulation of triaxial tests on coir fibre reinforced clay was conducted by [8].…”
Section: Introductionmentioning
confidence: 99%
“…Coir is useful in different applications as reinforcing material in soil due its high lignin content [5]. Many researchers [1][2][3][4][5][6][7][8][9][10] have shown that coir fibre reinforcement can significantly improve the engineering properties of soil. But the presence of the pectins, lignin, hemicellulose, silica and pith on the surface of these fibres results in poor interaction with the soil [3].…”
Section: Introductionmentioning
confidence: 99%